Method for improving performance of rare earth orthosilicate scintillation crystal

Through corrosion, plasma implantation and annealing diffusion treatment of rare earth orthosilicate scintillation crystals, the problem of insufficient performance in the existing technology is solved, the light output, attenuation time and energy resolution are significantly improved, and the afterglow intensity is reduced. The demand for high-performance scintillation crystals.

CN119194617APending Publication Date: 2024-12-27SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410980177.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing rare earth orthosilicate scintillation crystals still cannot meet the application requirements under high performance requirements, and performance has become a bottleneck restricting the development of related fields.

Method used

The corrosion, plasma implantation and annealing diffusion methods are used to form rare earth orthosilicate scintillation crystals through the corrosion liquid to expose defects, plasma implantation fills the oxygen vacancy defects, and oxygen ions are deeply penetrated into the crystal through annealing diffusion to improve crystal performance.

Benefits of technology

The light output is increased by 10% to 40%, the attenuation time is accelerated by 10% to 50%, the quality factor is increased by 20% to 90%, the energy resolution is optimized by 5% to 55%, and the afterglow intensity is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194617A_ABST
    Figure CN119194617A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of artificial crystals and radiation detection, and relates to a method for improving the performance of a rare earth orthosilicate scintillation crystal. The method for improving the performance of the rare earth orthosilicate scintillation crystal comprises the following steps: carrying out corrosion, plasma injection and annealing diffusion on the rare earth orthosilicate scintillation crystal, and finally realizing the improvement of the performance of the rare earth orthosilicate scintillation crystal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for improving the performance of a rare earth orthosilicate scintillation crystal, and belongs to the technical field of artificial crystals and radiation detection. Background Art

[0002] Inorganic scintillator crystal is a crystalline energy converter that can convert the energy of high-energy photons (X / γ rays) or particles (protons, neutrons, etc.) into easily detectable ultraviolet / visible photons. Detectors with inorganic scintillator crystal as the core are widely used in high-energy physics, nuclear physics, space physics, nuclear medicine diagnosis (X-CT, PET), geological exploration and safety inspection. Rare earth orthosilicate scintillator crystal has the advantages of high light output, fast attenuation, excellent energy resolution and radiation resistance, making it the preferred material in the field of radiation detection.

[0003] With the rapid development of particle physics and high-end nuclear medical imaging, higher requirements are placed on the performance of scintillation crystals. 2+ Ion-doped LSO:Ce crystals have achieved a 5% to 26% increase in light yield, a 44% to 57% increase in quality factor, and a 15% to 30% optimization in energy resolution (IEEE Trans. Nucl. Sci. 2009, 56(5), 2960-2965; IEEE Trans. Nucl. Sci. 2009, 56(5): 2972-2978). They have become the preferred component for engineering applications of scintillation crystals in the past decade. However, they still cannot meet the demand for high-performance scintillation crystals at the application end. The performance of scintillation crystals has become the main bottleneck restricting the development of related fields. Summary of the invention

[0004] In order to better solve the above problems, the present invention provides a method for improving the performance of rare earth orthosilicate scintillation crystals, comprising: subjecting the rare earth orthosilicate scintillation crystals to corrosion, plasma injection and annealing diffusion, thereby ultimately achieving the improvement of the performance of the rare earth orthosilicate scintillation crystals.

[0005] Preferably, the chemical composition of the rare earth orthosilicate scintillating crystal is RE 2-2x-y SiO5:xCe,yNi; wherein RE is a rare earth ion, and the RE is selected from at least one of Lu and Y; 0<x≤0.05, 0≤y≤0.05.

[0006] Furthermore, preferably, 0.0003≤x≤0.005 or / and 0.0005≤y≤0.02.

[0007] Preferably, the rare earth orthosilicate scintillation crystal is prepared by a pulling method, a crucible descent method, a temperature gradient method, a heat exchange method, a kyberyzing method, a top seed crystal method, a flux crystal growth method or a micro-pull-down method.

[0008] Preferably, the composition of the etching solution used for the etching treatment is at least one of phosphoric acid and hydrofluoric acid accompanied by at least one of sulfuric acid and hydrochloric acid; the concentration of the phosphoric acid is ≥70wt.%; the concentration of the hydrofluoric acid is ≥20wt.%; the concentration of the sulfuric acid is ≥80wt.%; the concentration of the hydrochloric acid is ≥30wt.%; preferably, the volume ratio of (phosphoric acid + hydrofluoric acid): (sulfuric acid + hydrochloric acid) in the etching solution is (1-5):1.

[0009] Preferably, the temperature of the corrosion treatment is room temperature to 250°C; the time of the corrosion treatment is 5 minutes to 10 hours; preferably, the corrosion treatment is carried out in a closed pressure-resistant container. In order to shorten the treatment time, the corrosion treatment can be carried out in a closed pressure-resistant container.

[0010] Preferably, the parameters of the plasma implantation process include: the implanted ions are oxygen ions; the energy of the oxygen ion implantation is 5keV to 1000keV, and the total dose is 10 16 ions / cm 2 ~10 18 ions / cm 2 ; The temperature of the injected rare earth orthosilicate scintillation crystal is -20℃~300℃.

[0011] Preferably, the atmosphere of the annealing treatment is air; the temperature of the annealing treatment is 300-1400° C.; and the time of the annealing treatment is 3-50 hours.

[0012] Preferably, when the thickness of the rare earth orthosilicate scintillator crystal is greater than 5 mm, the plasma implantation-annealing diffusion is repeated at least twice.

[0013] In the second aspect, the present invention provides a rare earth orthosilicate scintillation crystal prepared according to the above method. Compared with the untreated rare earth orthosilicate scintillation crystal, the light output of the obtained rare earth orthosilicate scintillation crystal is increased by 10% to 40%, the decay time is accelerated by 10% to 50%, the quality factor (light output or the ratio of light yield to decay time) is increased by 20% to 90%, the energy resolution is optimized by 5% to 55%, and the afterglow intensity is reduced by 1 to 2 orders of magnitude.

[0014] In a third aspect, the present invention provides an application of a rare earth orthosilicate scintillation crystal in the field of radiation detection, characterized in that the radiation detection field includes: high energy physics, particle detection, nuclear physics, space physics, nuclear medicine imaging (X or gamma-ray imaging, such as X-CT, PET, TOF-PET, PET-CT, PET-MRI, etc.), geological exploration and safety audit.

[0015] Beneficial effects of the present invention: The modification method of the present invention achieves comprehensive optimization of comprehensive performance, including improvement of light output or light yield, acceleration of decay time, improvement of quality factor (ratio of light output or light yield to decay time), optimization of energy resolution, and reduction of afterglow intensity. Compared with the currently commonly used direct annealing method, the processing temperature is reduced, the processing time is shortened, and the crystal performance is improved more significantly. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 To prepare the X-ray diffraction pattern of the sample in Example 1; Figure 2 To prepare the transmission spectrum of the sample in Example 1 in the range of 300-800nm; Figure 3 To prepare a multi-channel energy spectrum of the sample in Example 1 to characterize the crystal light output; Figure 4 To prepare the curve of the afterglow intensity of the sample in Example 1 as a function of the excitation stop time; Figure 5 To prepare the sample in Example 1 for characterizing crystal defects by thermoluminescence; Figure 6 Multi-channel energy spectra of samples of Example 2 and Comparative Example 5 were prepared to characterize the light output of the crystals. DETAILED DESCRIPTION

[0017] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0018] In the present disclosure, the chemical formula of the rare earth orthosilicate scintillating crystal is RE 2-2x-y SiO5:xCe,yNi. RE is a rare earth ion, and the RE is selected from at least one of Lu and Y; 0<x≤0.05, 0≤y≤0.05. RE is Lu or Y or Lu and Y are miscible in any proportion.

[0019] The following is an exemplary description of a method for preparing a rare earth orthosilicate scintillation crystal.

[0020] According to the chemical formula of the ingredients designed for the rare earth orthosilicate scintillating crystal with fully optimized comprehensive performance, Ni oxide (NiO or Ni2O3), CeO2, SiO2 and RE oxide are weighed and mixed to obtain a mixed powder.

[0021] The mixed powder is heated to melt, and the crystal is grown by using a Czochralski method, a crucible descent method, a temperature gradient method, a heat exchange method, a kyberyzing method, a top seed crystal method, a flux crystal growth method or a micro-pull-down method.

[0022] Comprehensive performance is fully optimized by conventional annealing, including: light output increased by 5% to 35%, decay time accelerated by 3% to 45%, quality factor increased by 15% to 75% (ratio of light output or light yield to decay time), energy resolution optimized by 1% to 40%, and afterglow intensity reduced by 1 to 2 orders of magnitude. When RE does not contain Lu, rare earth orthosilicate scintillator crystals with comprehensive performance optimization are directly obtained without annealing. When RE contains Lu, the prepared crystal is placed in a muffle furnace for annealing: keep warm in air at 1000°C to 1400°C at a heating / cooling rate of 1 to 10°C / min. The heat preservation time is determined by the crystal thickness, preferably 4 to 10h / mm. After the cooling is completed, a rare earth orthosilicate scintillator crystal with comprehensive performance optimization is obtained.

[0023] In the present invention, a modification method of "corrosion treatment-plasma injection treatment-annealing treatment" is adopted to improve the performance of rare earth orthosilicate scintillation crystal.

[0024] Etching: The purpose is to expose the defects of the rare earth orthosilicate scintillator crystal so that the defects are exposed to improve the efficiency of ion implantation. The composition of the etching solution used is at least one of phosphoric acid and hydrofluoric acid accompanied by at least one of sulfuric acid and hydrochloric acid. The temperature of the etching treatment can be room temperature to 250°C. The time of the etching treatment can be 5 minutes to 10 hours.

[0025] Plasma injection: The purpose is to inject a large amount of oxygen ions into the crystal surface and into the depth of the crystal along the defect outcrop to fill the oxygen vacancy defects in the crystal. The parameters of the plasma injection treatment include: the injected ions are oxygen ions; the energy of oxygen ion injection is 5keV~1000keV, and the total dose is 10 16 ions / cm 2 ~10 18 ions / cm 2 ; The temperature of injecting rare earth orthosilicate scintillation crystal is -20℃~300℃; The injection method is double-sided injection.

[0026] Annealing diffusion: The purpose is to diffuse the injected oxygen ions into a deeper crystal thickness while eliminating defects. The atmosphere of the annealing treatment is air. The temperature of the annealing treatment is 300-1400°C. The annealing treatment time is 3-50 hours. If the annealing temperature is too high, most of the oxygen ions will escape, and the performance of the resulting crystal will be limited. If the annealing temperature is too low, the oxygen ions will only penetrate into the crystal to a limited extent, and the performance of the resulting crystal will be limited.

[0027] In the present invention, the thickness of the rare earth orthosilicate scintillator crystal used is ≤5 mm. If the thickness is greater than 5 mm, the "plasma injection-annealing diffusion" step needs to be repeated at least twice.

[0028] In the present invention, the modification method of "corrosion-plasma injection-annealing diffusion" is adopted to achieve comprehensive optimization of comprehensive performance including: light output is increased by 10% to 40%, decay time is accelerated by 10% to 50%, quality factor is improved (ratio of light output or light yield to decay time) by 20% to 90%, energy resolution is optimized by 5% to 55%, and afterglow intensity is reduced by 1 to 2 orders of magnitude.

[0029] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0030] Preparation Example 1: Growth of Ni-doped YSO:Ce single crystal Single crystal growth by Czochralski method: According to the chemical formula Y 2-0.002--y SiO5: 0.1% Ce, yNi design ingredients, molar ratio NiO: CeO2: SiO2: Y2O3 = 2y: 0.002: 1: 0.999-y / 2 ingredients (y = 0, 0.00001, 0.0001, 0.0005, 0.001, 0.003, 0.006, 0.015, 0.02, 0.05), fully mixed to obtain a mixture. The mixture was pressed into a block under 250MPa cold isostatic pressing, placed in an iridium crucible, and fully melted by induction heating. After seed crystal inoculation, single crystals of preset size were grown from the melt while rotating (5-20rpm) and pulling (1-5mm / h), and YSO: Ce single crystals doped with different concentrations of Ni were obtained.

[0031] Preparation Example 2: (Growth of Ni-doped LYSO:Ce single crystal) Single crystals are grown using the Czochralski method: According to the chemical formula Lu 2-0.2-0.002-y Y 0.2SiO5: 0.1% Ce, yNi design ingredients, molar ratio NiO: CeO2: SiO2: Y2O3: Lu2O3 = 2y: 0.002: 1: 0.1: 0.899-y / 2 ingredients (y = 0, 0.00001, 0.0001, 0.0005, 0.001, 0.003, 0.006, 0.015, 0.02, 0.05), fully mixed to obtain a mixture. The mixture was pressed into a block under 250MPa cold isostatic pressing, placed in an iridium crucible, and fully melted by induction heating. After seed crystal inoculation, single crystals of preset size were grown from the melt while rotating (5-20rpm) and pulling (1-5mm / h), and different concentrations of Ni-doped LYSO: Ce single crystals were obtained.

[0032] Example 1 (1) Corrosion: The Ni-doped LYSO:Ce single crystal (y=0.006) obtained in Preparation Example 2 was immersed in a mixed acid solution (parts means parts by volume) consisting of 3 parts of phosphoric acid (phosphoric acid concentration ≥ 85 wt.%), 1 part of sulfuric acid (sulfuric acid concentration ≥ 98 wt.%), and 1 part of hydrochloric acid (hydrochloric acid concentration ≥ 35 wt.%), maintained at 80° C. for 1 hour, and then washed and dried; (2) Plasma implantation: The Ni-doped LYSO:Ce single crystal (y=0.006) that has been etched is implanted with oxygen ions. The parameters of the oxygen ion implantation include: 100 keV, total dose of 10 16 ions / cm 2 ; The temperature of the injected rare earth orthosilicate scintillator crystal is 200°C; (3) Annealing diffusion: The Ni-doped LYSO:Ce single crystal (y=0.006) after plasma injection treatment was annealed at 300° C. for 20 hours in an air atmosphere.

[0033] Example 2 The method for improving the performance of rare earth orthosilicate scintillation crystal in this embodiment 2 is similar to that in embodiment 1, with the only difference being that in step (3): annealing is performed at 800° C. for 20 hours in an air atmosphere.

[0034] Example 3 The method for improving the performance of rare earth orthosilicate scintillation crystals in this embodiment 3 is similar to that in embodiment 1, with the only difference being that in step (3): annealing is performed at 1400° C. for 20 hours in an air atmosphere.

[0035] Example 4 The method for improving the performance of rare earth orthosilicate scintillator crystal in this embodiment 4 is similar to that in embodiment 1, except that: in step (2): the parameters of oxygen ion implantation include: 100 keV, total dose 10 17 ions / cm 2; The temperature of the injected rare earth orthosilicate scintillation crystal is 200℃.

[0036] Example 5 (1) Corrosion: The Ni-doped YSO:Ce single crystal (y=0.006) obtained in Preparation Example 1 was immersed in a mixed acid solution consisting of 3 parts of phosphoric acid (phosphoric acid ≥ 80 wt.%), 1 part of sulfuric acid (sulfuric acid ≥ 90 wt.%), and 1 part of hydrochloric acid (hydrochloric acid ≥ 30 wt.%) (parts means parts by volume) at 200° C. for 0.1 hour, and then washed and dried; (2) Plasma implantation: The Ni-doped YSO:Ce single crystal (y=0.006) that has been etched is implanted with oxygen ions. The parameters of the oxygen ion implantation include: 200 keV, total dose of 10 16 ions / cm 2 ; The temperature of the injected rare earth orthosilicate scintillator crystal is 300°C; (3) Annealing diffusion: The Ni-doped YSO:Ce single crystal (y=0.006) after plasma injection was annealed at 800° C. for 50 hours in an air atmosphere.

[0037] Example 6 (1) Etching: The Ni-doped YSO:Ce single crystal (y=0.006, 0.015) obtained in Preparation Example 1 was immersed in a mixed acid solution consisting of 3 parts of phosphoric acid (phosphoric acid ≥ 80 wt.%), 1 part of sulfuric acid (sulfuric acid ≥ 90 wt.%), and 1 part of hydrochloric acid (hydrochloric acid ≥ 30 wt.%) (parts means parts by volume) at 80° C. for 1 hour, and then washed and dried; (2) Plasma implantation: The Ni-doped YSO:Ce single crystal (y=0.006) that has been etched is implanted with oxygen ions. The parameters of the oxygen ion implantation include: 200 keV, total dose of 10 18 ions / cm 2 ; The temperature of the injected rare earth orthosilicate scintillator crystal is 300°C; (3) Annealing diffusion: The Ni-doped YSO:Ce single crystal (y=0.006) after plasma injection was annealed at 800° C. for 50 hours in an air atmosphere.

[0038] Comparative Example 1 The method for improving the performance of rare earth orthosilicate scintillating crystals in this comparative example 1 is similar to that in Example 1, except that there is no etching step.

[0039] Comparative Example 2 The method for improving the performance of rare earth orthosilicate scintillating crystals in Comparative Example 2 is similar to that in Example 1, except that there is no plasma injection step.

[0040] Comparative Example 3 The method for improving the performance of the rare earth orthosilicate scintillation crystal in this comparative example 3 is similar to that in Example 1, with the only difference being that in step (3): annealing is performed at 200° C. for 20 hours in an air atmosphere.

[0041] Comparative Example 4 The method for improving the performance of the rare earth orthosilicate scintillation crystal in this comparative example 4 is similar to that in Example 1, with the only difference being that in step (3): annealing is performed at 1500° C. for 20 hours in an air atmosphere.

[0042] Table 1: corrosion Plasma injection Annealing Diffusion Example 1 80℃、1h <![CDATA[100keV,10 16 ions / cm 2 ,200℃]]> 300℃ / 20h Example 2 80℃、1h <![CDATA[100keV,10 16 ions / cm 2 ,200℃]]> 800℃ / 20h Example 3 80℃、1h <![CDATA[100keV,10 16 ions / cm 2 ,200℃]]> 1400℃ / 20h Example 4 80℃、1h <![CDATA[100keV,10 17 ions / cm 2 ,200℃]]> 300℃ / 20h Example 5 200℃、0.1h <![CDATA[200keV,10 16 ions / cm 2 ,300℃]]> 800℃ / 50h Example 6 80℃、1h <![CDATA[200keV,10 18 ions / cm 2 ,300℃]]> 800℃ / 50h Comparative Example 1 - <![CDATA[100keV,10 16 ions / cm 2 ,200℃]]> 300℃ / 20h Comparative Example 2 80℃、1h - 300℃ / 20h Comparative Example 3 80℃、1h <![CDATA[100keV,10 16 ions / cm 2 ,200℃]]> 200℃ / 20h Comparative Example 4 80℃、1h <![CDATA[100keV,10 16 ions / cm 2 ,200℃]]> 100℃ / 20h .

[0043] Table 2 shows the performance parameters of the modified rare earth orthosilicate scintillation crystals of Preparation Example 2 (y=0, 0.6%), Examples 1-4 and Comparative Examples 1-4:

[0044] Table 3 shows the performance parameters of the rare earth orthosilicate scintillation crystals modified by Preparation Example 1 (y=0, 0.6%), Example 5 and Example 6:

[0045] Comparative Example 5 (Ni-doped LYSO:Ce single crystal annealing post-treatment) The Ni-doped LYSO:Ce single crystals with different concentrations obtained in Preparation Example 2 were placed in a muffle furnace, heated to 1200°C at a rate of 5°C / min in air and kept at this temperature for 50 hours, and then cooled to room temperature at a rate of 5°C / min to obtain annealed Ni-doped LYSO:Ce single crystals.

[0046] Comparative Example 6 (Ni-doped YSO:Ce single crystal annealing post-treatment) The Ni-doped YSO:Ce single crystals with different concentrations obtained in Preparation Example 1 were placed in a muffle furnace, heated to 1200°C at a rate of 5°C / min in air and kept at that temperature for 50 hours, and then cooled to room temperature at a rate of 5°C / min to obtain annealed Ni-doped YSO:Ce single crystals.

[0047] from Figure 1 It can be seen that Ni doping causes the diffraction peak of YSO:Ce crystal to shift to a high angle, indicating that Ni replaces Y ions and reduces the unit cell volume, because the Ni ion radius is smaller than the Y ion radius and much larger than the Si ion radius.

[0048] from Figure 2 It can be seen that Ni doping will produce absorption at 500-700nm, which corresponds to RE 2-2x-y The slow emission band of Ce in SiO5:xCe crystal absorbs the slow emission band components, and the crystal emits light faster.

[0049] From Table 1, Table 2 and Table 3, we can see that RE 2-2x-y The comprehensive performance of SiO5:xCe,yNi rare earth orthosilicate scintillator crystal is fully optimized through the modification method of "corrosion-plasma injection-annealing diffusion": light output is increased by 10% to 40%, decay time is accelerated by 10% to 50%, quality factor is increased by 20% to 90%, energy resolution is optimized by 5% to 55%, and annealing temperature is significantly reduced.

[0050] from Figure 3 From the light output results in Table 4, it can be seen that Ni doping can increase the light output of YSO:Ce single crystal by up to 33.6%, and too high Ni doping concentration (y>1.5%) will greatly weaken its light output; combined with Table 5, it can be seen that the annealing post-treatment process of Ni-doped YSO:Ce single crystal has a slight improvement on light output, but the effect is not obvious. Further, combined with Table 3, it can be seen that the comprehensive performance can be further significantly improved by the modification method of "etching-plasma injection-annealing diffusion", which is significantly better than the conventional annealing treatment method.

[0051] from Figure 4 It can be seen that Ni doping reduces the afterglow intensity of YSO:Ce single crystal by 1 to 2 orders of magnitude at the same time when the excitation source stops exciting.

[0052] from Figure 5 It can be seen that Ni doping significantly reduces the thermoluminescence peak intensity of YSO:Ce single crystal, indicating that Ni doping greatly reduces the concentration of electron traps (i.e. defects) inside the crystal, which is the root cause of the overall optimization of its comprehensive performance.

[0053] From Table 3, Table 4, Table 5 and Figure 4 It can be seen that Ni doping and "etching-plasma injection-annealing diffusion" can optimize the light output, decay time, quality factor, energy resolution, and afterglow performance of YSO:Ce single crystals, but the conventional annealing post-treatment process has no obvious effect on improving these properties. Among them, the quality factor has the largest increase, reaching 89.2%, which is the best level reported internationally.

[0054] from Figure 6From the light output results in Tables 6 and 7, it can be seen that before the Ni-doped LYSO:Ce single crystal is annealed, the light output improvement ratio is less than 5%, and there is a deterioration phenomenon; after the Ni-doped LYSO:Ce single crystal is annealed, the light output is improved by 5% to 17.1%, indicating that the post-annealing treatment process is particularly important for improving the light output of Ni-doped LYSO:Ce single crystal; combined with Tables 1 and 2, it can be seen that "corrosion-plasma injection-annealing diffusion" can further increase the light output to 39.6%, and the annealing temperature is significantly reduced.

[0055] From Table 2, Table 6, Table 7 and Table 8, it can be seen that although Ni doping can optimize the light output, decay time, quality factor, energy resolution and afterglow (intensity reduced by 1 to 2 orders of magnitude) of LYSO:Ce single crystal after conventional annealing, the “etching-plasma injection-annealing diffusion” makes its performance optimization more significant, among which the energy resolution is optimized by 51.7%, which is greater than the currently recognized best component Lu 1.998-2v The energy resolution optimization ratio (30%) that can be achieved by SiO5:0.1%Ce,vCa is the best level in the world at present, as shown in Table 9.

[0056] Table 4 shows the light output, decay time, quality factor, energy resolution and improvement of the Ni-doped YSO:Ce single crystal grown in Preparation Example 1:

[0057] Table 5 shows the light output, decay time, quality factor, energy resolution and improvement of the YSO:Ce single crystals doped with different concentrations of Ni in Comparative Example 6 after conventional annealing:

[0058] Table 6 shows the light output, decay time, quality factor, energy resolution and improvement of the Ni-doped LYSO:Ce single crystal grown in Preparation Example 2:

[0059] Table 7 shows the light output, decay time, quality factor, energy resolution and improvement of LYSO:Ce single crystals doped with different concentrations of Ni in Comparative Example 5 after conventional annealing:

[0060] Table 8 shows the afterglow level of LYSO:Ce single crystals doped with different concentrations of Ni after conventional annealing in Example 2 and Comparative Example 5:

[0061] Table 9 shows the publicly recognized best components Lu1.998-2v SiO5: 0.1% Ce, vCa energy resolution and its optimized ratio (IEEE Trans. Nucl. Sci. 2009, 56 (5): 2972-2978): v(%) Energy resolution (%) Energy resolution optimization ratio (%) 0 10.5 0 0.1 7.4 29.5 0.2 7.35 30.0 0.3 8.2 21.9 0.4 8.9 15.2 .

Claims

1. A method for improving the performance of rare earth orthosilicate scintillation crystals, characterized in that: include: The rare earth orthosilicate scintillation crystal is subjected to corrosion, plasma injection and annealing diffusion, and finally the performance of the rare earth orthosilicate scintillation crystal is improved.

2. The method for improving the performance of rare earth orthosilicate scintillation crystal according to claim 1, characterized in that: The chemical composition of the rare earth orthosilicate scintillation crystal is RE 2-2x-y SiO5:xCe,yNi; wherein RE is a rare earth ion, and the RE is selected from at least one of Lu and Y; 0<x≤0.05, 0≤y≤0.

05.

3. The method for improving the performance of rare earth orthosilicate scintillation crystal according to claim 2, characterized in that: 0.0003≤x≤0.005 or / and 0.0005≤y≤0.

02.

4. The method for improving the performance of rare earth orthosilicate scintillation crystals according to any one of claims 1 to 3, characterized in that: Rare earth orthosilicate scintillation crystals are prepared by using a Czochralski method, a crucible descent method, a temperature gradient method, a heat exchange method, a kyberyzing method, a top seed crystal method, a flux crystal growth method or a micro-pull-down method.

5. The method for improving the performance of rare earth orthosilicate scintillation crystal according to any one of claims 1 to 4, characterized in that: The etching solution used in the etching treatment is composed of at least one of phosphoric acid and hydrofluoric acid and at least one of sulfuric acid and hydrochloric acid; The concentration of phosphoric acid is ≥70wt.%; the concentration of hydrofluoric acid is ≥20wt.%; the concentration of sulfuric acid is ≥80wt.%; the concentration of hydrochloric acid is ≥30wt.%; Preferably, the volume ratio of (phosphoric acid + hydrofluoric acid): (sulfuric acid + hydrochloric acid) in the etching solution is (1-5):

1.

6. The method for improving the performance of rare earth orthosilicate scintillation crystals according to any one of claims 1 to 5, characterized in that: The corrosion temperature is room temperature to 250° C.; the corrosion treatment time is 5 minutes to 10 hours; preferably, the corrosion treatment is carried out in a closed pressure-resistant container.

7. The method for improving the performance of rare earth orthosilicate scintillation crystals according to any one of claims 1 to 6, characterized in that: The parameters of the plasma implantation process include: the implanted ions are oxygen ions; the energy of the oxygen ion implantation is 5keV to 1000keV, and the total dose is 10 16 ions / cm 2 ~10 18 ions / cm 2 ; The temperature of the injected rare earth orthosilicate scintillation crystal is -20℃~300℃.

8. The method for improving the performance of rare earth orthosilicate scintillation crystals according to any one of claims 1 to 7, characterized in that: The atmosphere of the annealing treatment is air; the temperature of the annealing treatment is 300 to 1400° C.; and the time of the annealing treatment is 3 to 50 hours.

9. A rare earth orthosilicate scintillation crystal prepared according to the method of any one of claims 1 to 8.

10. Use of the rare earth orthosilicate scintillation crystal according to claim 9 in the field of radiation detection, characterized in that: The radiation detection field includes: high energy physics, particle detection, nuclear physics, space physics, nuclear medicine imaging, geological exploration and safety audit.

Citation Information

Cited By

  • Rare earth silicon germanate scintillating material as well as preparation method and application thereof

    CN120818364A